As operações de paz da ONU e os atores regionais: arranjos de cooperação e desafios - Saint-Pierre, Héctor Luis (2017)
In the context of the expansion of the United Nations security agenda in the post-Cold War era, we analyze the modalities of cooperation between the institution and regional actors in the field of peace operations, pointing out some challenges of the joint efforts at international, regional and state levels.